EXISTENCE OF MARRIAGE IN THE SASAK TRIBE IN LOMBOK (MERARIQ) WITHIN THE ESTUARY OF LEGAL PLURALISM - Wahyuddin Lukman (Fakultas Hukum Universitas Mataram, 2014)
Man is basically a creature of God who has relation (through worship) to God (fardhu a’in)and relation to other creatures as social beings (fard kifayah). This dual relationship will asconsequence make a various instruments of what-the-so-called Legal Pluralism. The LegalPluralism in human life is a bind positioning the human to commit with what are containedin each instrument, even though the instruments are mostly abstract and are only dialecticalsymbols that have a strong energy leading the physical nd spiritual side of human to obey theGod and to do anything on behalf of the “theological and Social Faith” in order to obtain thephysical and spiritual peace. To achieve those needs , human his life as a creature implementthe legal pluralism, which is believed to serve as an investment in order that his dual function ofcreation remain maintained and qualified. The instance of this is the implementation of legalpluralism in the procession of “Merariq” (Marriage) in indigenous people the Lombok Sasaktribe. In that procession, three laws are implemented; religious teaching, traditional law, andState law all of which are integratedly applied in the process (3 in 1).Keywords : Existence, Legal Pluralism, Merariq